Attention Management - Lipnowski, Elliot and Dong Wei (The American Economic Review: Insights)
Attention costs can cause some information to be ignored and decisions to be imperfect. Can we improve the material welfare of a rationally inattentive agent by restricting his information in the first place? In our model, a well-intentioned principal provides information to an agent for whom information is costly to process, but the principal does not internalize this cost. We show that full information is universally optimal if and only if the environment comprises one issue. With multiple issues, attention management becomes optimal: the principal restricts some information to induce the agent to pay attention to other aspects.- Reproduced
Keywords: Asymmetric and Private Information; Mechanism Design